IN VITRO MULTIPLICATION OF JABON (ANTHOCEPHALUS CADAMBA (ROXB)) ON VARIOUS CONCENTRATION OF BAP AND IAA - Asgar Taiyeb; Baharuddin Baharuddi (Tadulako University, 2017)
One of problems in the Jabon propagation is the availability of seeds both quality and quantity. Tissue culture technology is one of the alternatives that can be used for the supply of Jabonseeds to produce organs of plants (buds, leaves, roots). The success of plant tissue culture techniques is determined by the condition of explants, a supportive environment and the addition of growth regulators are expected to provide a response to the cultured explants. This study aimed to know the effect of Benzyl Amino Purine (BAP) and Indole Acetic Acid (IAA) to in vitro multiplication of Jabon. This research conducted at the Laboratory of Forestry Sciences, Faculty of Forestry, University of Tadulako from March to May 2015. Using a completely randomized design with treatments: 0.1 mg / l IAA + 1 mg / l BAP (JB1), 0.1 mg / l IAA + 1.5 mg / l BAP (JB2), 0.1 mg / l IAA + 2 mg / l BAP ( JB3) and 0.1 mg / l IAA + 2.5 mg / l BAP (JB4). Each treatment was repeated three times to obtain 12 experimental units. The results showed that the difference in response Jabon of treatment tested was the highest number of buds and leaves were in the media added 0.1 mg / l IAA + 1.5 mg / l BAP. Furthermore, the formation of callus obtained in media which added 0.1 mg / l IAA + 1 mg / l BAP.